Combination treatment of elevated UVB radiation, CO2 and temperature has little effect on silver birch (Betula pendula) growth and phytochemistry. Issue 4 (15th April 2013) - Lavola, Anu; Nybakken, Line; Rousi, Matti; Pusenius, Jyrki; Petrelius, Mari; Kellomäki, Seppo; Julkunen‐Tiitto, Riitta
<x xml:space="preserve">Abstract</x> Elevations of carbon dioxide, temperature and ultraviolet‐B (UBV) radiation in the growth environment may have a high impact on the accumulation of carbon in plants, and the different factors may work in opposite directions or induce additive effects. To detect the changes in the growth and phytochemistry of silver birch (Betula pendula) seedlings, six genotypes were exposed to combinations of ambient or elevated levels of CO2, temperature and UVB radiation in top‐closed chambers for 7 weeks. The genotypes were relatively similar in their responses, and no significant interactive effects of three‐level climate factors on the measured parameters were observed. Elevated UVB had no effect on growth, nor did it alter plant responses to CO2 and/or temperature in combined treatments. Growth in all plant parts increased under elevated CO2, and height and stem biomass increased under elevated temperature. Increased carbon distribution to biomass did not reduce its allocation to phytochemicals: condensed tannins, most flavonols and phenolic acids accumulated under elevated CO2 and elevated UVB, but this effect disappeared under elevated temperature. Leaf nitrogen content decreased under elevated CO2. We conclude that, as a result of high genetic variability in phytochemicals, B. pendula seedlings have potential to adapt to the tested environmental changes. The induction in protective flavonoids under UVB radiation together with the positive impact of elevated CO2 and temperature mitigates possible UVB stress effects, and thus atmospheric CO2 concentration and temperature are the climate change factors that will dictate the establishment and success of birch at higher altitudes in the future.